Clinical practice guidelines. Some aspects related to their devising and implementation. - Alfredo Darío Espinosa Brito (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2009)
This article deals with the role of clinical practice guidelines within hospital or out-patient management these days, along with aspects related to the latest auxiliary tools of medical care, such as: origins, their relationship to evidence-based medicine, their requirements, methods to devise, implement and assess them, as well as the most important sites to consult the best current guidelines. The idea for the present article comes from these guidelines' growing, widespread use in medical care.